Study pemodelan Performa Pendinginan Evaporasi Pada Gedung Auditorium Ums Dengan Computational Fluids Dynamics (CFD) - Adinata, Andrey Trias; , Ir. Sarjito, MT, Ph.D (2017)
The building is a wide area that canaccomodate hundreds of people. So that the temperature in the building in the condition of the comfortable then appears some research about capturing the wind (wind catcher) and nozzle. This research on the model of the building that will be simulated is the equivalent of the Auditorium HM. Djasman in Muhammadiyah University Surakarta. The modeling is done using Computational Fluid Dynamic (CFD) one technique is to perform the addition on the top of the building in the form of wind catcher and nozzle. The research started with perform validation with research Abdullah (2016). Validation is performed by making a wind catcher and the building and make the electrical on the wall of the building and the electrical on the building ventilation. Do running and measured massflow on plene under the wind catcher. Research continued through testing with do variations in wind speed 0.5 m/s; 1.5 m/s; 2.5 m/s; 3.5 m/s; 4.5 m/s; and 5.5 m/s, air humidity 5%, 10%, 15%, and 25%, and the temperature of the outside air which represent in several cities in Indonesia. After running, use function calculator on the point and plane 5 m above the floor, obtained the results of the most optimal wind speed on 4.5 m/s, air humidity the most optimal is 5%. Then RH air most low in Manado city. Key Words : Wind catcher, CFD, nozzle, temperature